A single centre prospective cohort study addressing the effect of a rule-in/rule-out troponin algorithm on routine clinical practice. Issue 5 (1st August 2019) - Marjot, Jack; Kaier, Thomas E; Henderson, Katherine; Hunter, Laura; Marber, Michael S; Perera, Divaka
Abstract: Aims: In 2015, the European Society of Cardiology introduced new guidelines for the diagnosis of acute coronary syndromes in patients presenting without persistent ST-segment elevation. These guidelines included the use of high-sensitivity troponin assays for 'rule-in' and 'rule-out' of acute myocardial injury at presentation (using a '0 hour' blood test). Whilst these algorithms have been extensively validated in prospective diagnostic studies, the outcome of their implementation in routine clinical practice has not been described. The present study describes the change in the patient journey resulting from implementation of such an algorithm in a busy innercity Emergency Department. Methods and results: Data were prospectively collected from electronic records at a large Central London hospital over seven months spanning the periods before, during and after the introduction of a new high-sensitivity troponin rapid diagnostic algorithm modelled on the European Society of Cardiology guideline. Over 213 days, 4644 patients had high-sensitivity troponin T measured in the Emergency Department. Of these patients, 40.4% could be 'ruled-out' based on the high-sensitivity troponin T concentration at presentation, whilst 7.6% could be 'ruled-in'. Adoption of the algorithm into clinical practice was associated with a 37.5% increase of repeat high-sensitivity troponin T measurements within 1.5 h for those patients classified as 'intermediate risk' on presentation. Conclusions: Introduction of a 0 hour 'rule-in' and 'rule-out' algorithm in routine clinical practice enables rapid triage of 48% of patients, and is associated with more rapid repeat testing in intermediate risk patients.